2015
DOI: 10.1136/heartjnl-2014-306737
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement and standard therapy in inoperable patients with aortic stenosis and low EF

Abstract: ClinicalTrials.gov Unique Identifier #NCT00530894.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
0
33
1
Order By: Relevance
“…1,11 Although these studies included patients with lesser degrees of LV systolic dysfunction (ie, EF 40%-50%), the general finding of a rapid recovery is similar: in PARTNER A, ≈50% of patients demonstrated early LVEF recovery (≥10% absolute increase in EF at 30-day follow-up after Sapien TAVR). Our finding of a high rate (62%) of early LVEF recovery may portend a role for the CoreValve TAVR procedure in these patients with low EF.…”
Section: Temporal Trends In Recovery Of Lvefmentioning
confidence: 88%
See 2 more Smart Citations
“…1,11 Although these studies included patients with lesser degrees of LV systolic dysfunction (ie, EF 40%-50%), the general finding of a rapid recovery is similar: in PARTNER A, ≈50% of patients demonstrated early LVEF recovery (≥10% absolute increase in EF at 30-day follow-up after Sapien TAVR). Our finding of a high rate (62%) of early LVEF recovery may portend a role for the CoreValve TAVR procedure in these patients with low EF.…”
Section: Temporal Trends In Recovery Of Lvefmentioning
confidence: 88%
“…All of these patients demonstrated contractile reserve with dobutamine echocardiography, as patients without adequate contractile reserve were not enrolled in these 2 trials. Contractile reserve was defined as an augmented mean gradient of >40 mm Hg with escalating doses of dobutamine (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) μg/kg per minute). Of note, simultaneous augmented LVEF was not considered a requirement for inclusion in the trials.…”
Section: Recovery Of Lvef: Time and Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…& We found that a subset of patients treated with standard therapy within the PARTNER trial experienced significant improvement in LV systolic function, symptoms, and 1-year survival. This observation was hypothesized to be due to the temporary benefits seen with BAV [72], although in the entire cohort, BAV was not associated with improvements in LV function [97•]. Importantly, benefits observed after BAV did not persist beyond 1 year, emphasizing the need for definitive therapy with AVR.…”
Section: Balloon Aortic Valvuloplastymentioning
confidence: 94%
“…Passeri et al showed effectiveness of transfemoral TAVR in improving survival among patients with mild-moderate LV dysfunction (EF >20%) and inoperable AS compared to standard medical therapy [16]. In a meta-analysis of 7,673 patients with severe AS who underwent TAVR, patients with a low stroke volume index (< 35ml/m2), low gradient and low EF (< 30%) had significant higher mortality at follow up.…”
Section: Discussionmentioning
confidence: 99%